Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pcbi.1009868
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq is not required to determine stable reference genes for qPCR normalization

Abstract: Assessment of differential gene expression by qPCR is heavily influenced by the choice of reference genes. Although numerous statistical approaches have been proposed to determine the best reference genes, they can give rise to conflicting results depending on experimental conditions. Hence, recent studies propose the use of RNA-Seq to identify stable genes followed by the application of different statistical approaches to determine the best set of reference genes for qPCR data normalization. In this study, ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Coenye (2021) reported that approximately 15%–20% of genes were nonconcordant (i.e., directionally opposite or one method resulted in differential expression and the other did not) when comparing differential expression results between qPCR and RNAseq. Sampathkumar et al (2022) also reported correlation coefficients typically ≥0.8 in terms of concordant differential expression (i.e., comparable magnitudes, directionally consistent) between the two approaches. Future studies should compare EcoToxChip differential expression (i.e., fold change) from an exposure experiment with corresponding RNAseq data to further explore this relationship and should include samples for fathead minnow and X. laevis .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Coenye (2021) reported that approximately 15%–20% of genes were nonconcordant (i.e., directionally opposite or one method resulted in differential expression and the other did not) when comparing differential expression results between qPCR and RNAseq. Sampathkumar et al (2022) also reported correlation coefficients typically ≥0.8 in terms of concordant differential expression (i.e., comparable magnitudes, directionally consistent) between the two approaches. Future studies should compare EcoToxChip differential expression (i.e., fold change) from an exposure experiment with corresponding RNAseq data to further explore this relationship and should include samples for fathead minnow and X. laevis .…”
Section: Resultsmentioning
confidence: 90%
“…A certain amount of discordance is expected given that qPCR genes with high C t values (e.g., >~32; low expressed) are less robust in general with regard to reproducibility given the constraints of PCR at later cycles and may therefore impact such correlative relationships. Other studies have reported that nonconcordant genes tend to: 1) be associated with transcript‐length bias, whereby longer transcripts have higher counts regardless of expression levels; 2) have fewer exons; and 3) have low expression (i.e., a majority of reads stem from a small set of highly expressed genes and therefore discriminate against low‐expression genes) compared with concordant genes (Everaert et al, 2017; Sampathkumar et al, 2022). In addition, the number of poor quality and multimapping reads was higher for nonconcordant genes.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, potentially the 16S rRNA gene may not be a proper reference for this biofilm community. According to Sampathkumar and colleagues, sometimes choosing the reference based only on RNA-seq data may be an erroneous approach [ 43 ], and additional bioinformatic studies are needed. Additionally, potentially the genes we found are small, have few exons, and are actually expressed lower compared to genes with consistent expression measurements between the two methods, according to another study [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome sequencing is an important research method for gene expression analysis and screening differentially expressed and functional genes. Notably, screening reference genes using transcriptome data is an effective experimental method for screening reference genes in non-model species ( 32 34 ). RPS4X and RPS6 are more stable than traditionally used housekeeping genes in the goat rumen ( 35 ), while NCBP3, SDHA , and PTPRA are more stable than traditionally used housekeeping genes in goat skin tissue ( 10 ).…”
Section: Discussionmentioning
confidence: 99%